2019 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2019
DOI: 10.1109/iros40897.2019.8967523
|View full text |Cite
|
Sign up to set email alerts
|

Contact Skill Imitation Learning for Robot-Independent Assembly Programming

Abstract: Robotic automation is a key driver for the advancement of technology. The skills of human workers, however, are difficult to program and seem currently unmatched by technical systems. In this work we present a data-driven approach to extract and learn robot-independent contact skills from human demonstrations in simulation environments, using a Long Short Term Memory (LSTM) network. Our model learns to generate error-correcting sequences of forces and torques in task space from object-relative motion, which in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 68 publications
0
10
0
1
Order By: Relevance
“…Perhaps the most promising results, however, come from the sequence modeling domain. Recurrent neural networks show up in earlier scientific literature periodically, such as in predicting a time-series of robot end-effector loads in an assembly task [Scherzinger et al, 2019] and learning latent action plans from large, uncategorized play data sets [Lynch et al, 2020]. But current state-of-the-art performance across a wide variety of sequence prediction tasks -among them imitation learning in a robotics context -is given by combining a large, universal transformer model with embedding schemes specific to various data modalities [Reed et al, 2022].…”
Section: Related Workmentioning
confidence: 99%
“…Perhaps the most promising results, however, come from the sequence modeling domain. Recurrent neural networks show up in earlier scientific literature periodically, such as in predicting a time-series of robot end-effector loads in an assembly task [Scherzinger et al, 2019] and learning latent action plans from large, uncategorized play data sets [Lynch et al, 2020]. But current state-of-the-art performance across a wide variety of sequence prediction tasks -among them imitation learning in a robotics context -is given by combining a large, universal transformer model with embedding schemes specific to various data modalities [Reed et al, 2022].…”
Section: Related Workmentioning
confidence: 99%
“…Nevertheless, it is difficult to generalize over multiple tasks, and trajectories are usually not reusable. Recent works in the field of kinesthetic teaching and imitation learning try to generalize demonstrations, e.g., [19,37,59]. Those methods might be important in the future for acquiring robotic skills.…”
Section: Human Demonstrations and Learningmentioning
confidence: 99%
“…Successful implementations of forward dynamics-based control on industrial robots can be found e.g. in [27] for pure force control and in [9], [28] for compliance control. An application to motion control with a particular focus on sparsely sampled targets is presented in [10].…”
Section: Control Applicationsmentioning
confidence: 99%